2012
DOI: 10.1007/s11427-012-4310-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid organisms

Abstract: Polyploids are organisms with three or more complete chromosome sets. Polyploidization is widespread in plants and animals, and is an important mechanism of speciation. Genome sequencing and related molecular systematics and bioinformatics studies on plants and animals in recent years support the view that species have been shaped by whole genome duplication during evolution. The stability of polyploids depends on rapid genome recombination and changes in gene expression after formation. The formation of polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 83 publications
(114 reference statements)
2
65
0
6
Order By: Relevance
“…Recent polyploids have been identified in fishes and amphibians (Choleva and Janko, 2013;Gui and Zhou, 2010;Otto, 2007;Song et al, 2012) and some diploidized tetraploid species have been demonstrated in some teleost fish lineages including cyprinids, catostomids, and salmonids (Allendorf and Thorgaard, 1984;Collares-Pereira et al, 2013;Gui and Zhou, 2010;Yang and Gui, 2004), but the two recent rounds of polyploidy have been documented only in the polyploid gibel carp. Recent genome-wide studies have confirmed that the problem of genetic incompatibility raised by polyploidy may be resolved by the accumulation of diverse mutational changes to form a stable chimerical and diploidized genome (Buggs et al, 2011;Chen and Ni, 2006;Louis et al, 2012;Tate et al, 2009).…”
Section: Evolutionary Consequences Of Polyploidy In Gibel Carpmentioning
confidence: 99%
“…Recent polyploids have been identified in fishes and amphibians (Choleva and Janko, 2013;Gui and Zhou, 2010;Otto, 2007;Song et al, 2012) and some diploidized tetraploid species have been demonstrated in some teleost fish lineages including cyprinids, catostomids, and salmonids (Allendorf and Thorgaard, 1984;Collares-Pereira et al, 2013;Gui and Zhou, 2010;Yang and Gui, 2004), but the two recent rounds of polyploidy have been documented only in the polyploid gibel carp. Recent genome-wide studies have confirmed that the problem of genetic incompatibility raised by polyploidy may be resolved by the accumulation of diverse mutational changes to form a stable chimerical and diploidized genome (Buggs et al, 2011;Chen and Ni, 2006;Louis et al, 2012;Tate et al, 2009).…”
Section: Evolutionary Consequences Of Polyploidy In Gibel Carpmentioning
confidence: 99%
“…Polyploids contain three or more complete chromosome sets, which are widespread in plants and animals and are important for speciation [117]. Polyploid breeding refers to doubling cell genomes by artificial or natural mutagenesis to produce polyploid individuals, and then selected and fostered by persons to meet requirements.…”
Section: Polyploid Breedingmentioning
confidence: 99%
“…Physical and chemical methods artificially induce polyploidy work by inhibiting the exclusion of the first or second polar body in the oocytes or inhibiting the first cleavage of zygotes [117]. Gui et al [119] succeeded in inducing triploid Carassius auratus transparent colored var.…”
Section: Polyploid Breedingmentioning
confidence: 99%
“…WGDs have also been documented in other kingdoms, such as, for instance, three WGDs in the ciliate Paramecium tetraurelia (Aury et al 2006) and one WGD in the ancestor of the hemiascomycete Saccharomyces cerevisiae (Wolfe and Shields 1997). A systematic overview of WGD in invertebrates, amphibians, and reptiles is lacking, but several examples have been described, contradicting the classical notion that paleopolyploidies are absent in these lineages (Mable 2004;Song et al 2012).…”
mentioning
confidence: 99%